Pengaruh Pembiayaan Dana Baitul Maal Wat Tamwil (BMT) Teladan Terhadap Kinerja Usaha Mikro di Pasar Semolowaru Surabaya - Damayanti, Nurul Farida; Herianingrum, Sri (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This research aims to find out the influence of funding of BMT Teladan towards microenterprisesÂ performances in Semolowaruâs Market Surabaya. Questionnaires are used toÂ collect the primary data. The data is analyzed by using one of quantitative approachesÂ which is simple regressive analysis. The samples of the analysis are 30 BMT Teladan customersÂ who have been partners for at least one years. Purposive sampling is used as it eases theÂ researcher to take detailed informations and it also appropriate towards the aim of theÂ research.The result of the research shows that the BMT Teladan funding which covers Ijarah andÂ Murabahah financing are indeed influential towards micro-enterprises performances inÂ increasing earnings and asset of micro-enterpreneur in Semolowaruâs Market Surabaya.Â BMT Teladan shoud provide stronger internal factors for increasing the performances ofÂ micro-enterprises such as developing and empowering human resources (microenterpreneur).Â The successes and failures of an enterprise or a business relies on theÂ capability of its human resources especially in applying business strategy. In other words, theÂ success of an enterprise is determined by the quality of its human resources as microenterpreneurs.Â It is hoped for the next further research to use a broaderfactor (internal andÂ external) that influences the performance of micro-enterprises.